Aplikasi Model Rusle untuk Estimasi Kehilangan Tanah Bagian Hulu di Sub Das Garang, Jawa Tengah - Hanafi, Fahrudin; Pamungkas, Dany (Universitas Negeri Semarang, 2021)
The Garang watershed is one of the main rivers passing through Semarang City, Central Java. Garang uptream is mostly a buffer zone and a catchment area for the water and soil resources conservation of Semarang City and surroundings. This research is located in the upstream Garang watershed, with the aim of knowing the level of erosion or soil loss tolerance due to land use change.The erosion model is specific to sheet erosion which modeled with RUSLE (Revised Universal Soil Loss Equation) method. The data used are (R) ground rainfall from 7 hydrological stations for 10 years, (K) soil types derived from land form interpretation, (LS) length and slope from SRTM radar data, (CP) conservation and land cover derived using a multispectral supervised classification (maximum likelihood). The quality of modeling is maintained through validation of input data, such as the normal ratio method and consistency test of rain data, soil texture and color surveys for soil data, confusion matrices for land cover and slope validation.The research results of the upstream Garang watershed area of 1191,56 hectares (14.14%), the erosion that occurred was still below the allowable erosion limit, while the area of 7.232,67 hectares (85.86%) was erosion that occurred above the allowable erosion value. The average soil loss is 222 tonnes / ha / year with the potential for soil loss up to 39,236 tonnes per year or soil loss thickness of 3.8 cm. Even though it is within the threshold, this must be controlled considering the importance of the upstream Garang watershed, whose land cover has begun to change its function to agriculture and plantations on sloping land.